Hydrocolloid to Prevent Breakdown of Nares in Preterm Infants. Issue 1 (January 2015) - Morris, Lori D.; Behr, Jodi Herron; Smith, Sandra L.
Abstract Purpose: To determine if a double-barrier hydrocolloid dressing prevents trauma to the nares and columella in very low birthweight (VLBW) infants (<1, 500 grams) receiving heated humidified high-flow nasal cannula (HHHFNC) oxygen. Study Design and Methods: Retrospective two-group comparative study design. Sample: Medical records (N = 53) of VLBW infants receiving HHHFNC were reviewed. Control infants (n = 27) did not have a double-barrier hydrocolloid dressing. Intervention infants (n = 26) had a double-barrier hydrocolloid dressing. Groups were similar on sex, race, birthweight, and gestational age. Control infants were significantly older than intervention infants at study entry (4.3 weeks and 1.5 weeks, respectively, p = .001). Skin condition of nares was scored daily ranging from 3 (no breakdown) to 9 (extensive breakdown). Skin scores were abstracted from medical records at baseline then weekly for comparison over time. Results: There were no significant differences in skin scores between groups or over time. Week 1 mean skin score was 3.4 (±0.1) in both groups. Mean skin score at week 4 was 3.4 (±0.1) in Control infants and 3.1 (±0.08) in Intervention infants. Clinical Implications: HHHFNC is more frequently being used in infants of extreme prematurity. The dressing may have protected the more immature skin of the intervention infants; however, vigilant nursing observation of the infants' nares during HHHFNC cannot be ruled out. Nurses need adequate education on the consistent application of the hydrocolloid barrier and on documenting skin assessment scores each shift to promote skin protection in this vulnerable population.